The Impact Of Self-Actualization And Compensation Towards Multipurpose Cooperative Managers Work Performance In Semarang - Kusnilawati, Nunik; Murwanto, Haris; Ariefiantoro, Teguh (Universitas Semarang, 2018)
Article 33 of the 1945 Constitution of the Republic of Indonesia puts the cooperative as the pillar of our national economy. However, its contribution to national economy is hardly significant due to several constraints; among them is human resources.The purpose of the study is to analyze the impact of self-actualization and compensation towards the working performance of multi-purpose cooperative managers by using quantitative approach. This research used purposive sampling technique and collected a sample of 114 multi-purpose cooperative manager of 168 population using. Binary regression is used in descriptive statistics test.The results show that both self-actualization and compensation have significant influence towards the working performance of multi-purpose cooperative managers in Semarang.